EQ DAN AQ DALAM PENGEMBANGAN PROFESIONALISME PUSTAKAWAN - Nurohman, Aris (STAIN Ponorogo, 2013)
EQ had a role to give a strong certainty. It would haveadvantage to understand the reality of emotion instantly, and make appraisal shortly, so that one can show will be distrusted, who have to trust, who will suffer. While AQ will give a horizon and a lot new of tools to decrease adversity and to increase some oneâs qualities so they could face the continues change.EQ and AQ in developing of librarian profession will aid to self control and emotion management. By EQ and AQ will aid librarians able to manage self complexity, so it will bear intellectual, skill, behavior, leadership, good personality, smart, creative, progressive and broad horizon.